Sturge-Weber Disease - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1983)
ABSTRACT: Seurge- Weber Disease: A case report Sturge-Weber Disease is one of the congenital malforMations, in which we find naevus facialis, general or focal convulsion, mental retardation, and contralateral hemiparesis